Dampak Sosial Ekonomi pada Keluaga Penerima Manfaat (KPM) Program Keluarga Harapan (PKH) Exit Mandiri di Kecamatan Pagelaran Kabuoaten Pringsewu dalam Perspektif The Most Significant Change Technique (MSCt) - Ainun Oktavia Sari; Rahayu Sulistyowati; Ita Prihantika (Jurnal Administrativa, 2021)
The Conditional Cash Transfer (CCT) is a conditional social cash transfer program that provides assistance to Very Poor Households (RTSM) appointed as participants in the Conditional Cash Transfer program which is related to improving the quality of human life through education and health. This study aims to analyze the impact of Conditional Cash Transfers on ex-families who receive of Conditional Cash Transfers who go out independently in Pagelaran District with indicators of changes in economic conditions, changes in health quality, and changes in the quality of education. In evaluating the impact of this program, the researcher used the impact evaluation theory using The Most Significant Change technique (MSC) which is a participatory monitoring and evaluation technique that aims to obtain information about the most important changes in family life resulting from participation in poverty programs. The results of this study indicate that the Conditional Cash Transfer in Pagelaran District has a changing impact on the Former Beneficiary Family both positive and negative. Seen from the positive impact, the Former Beneficiary Family have experienced changes for the better, especially in the fields of economy and education. However, there has been change in the health sector because the informant of the Former Beneficiary Family in Pagelaran District was the recipient of assistance in the education sector. However, the negative side is the lack of compliance of former recipient families when they become participants in education.